Effect of Hardskill and Softskill on Employee Performance - Toni Maryanto; Umban Adi Jaya (Jurnal Adijaya Multidisplin, 2023)
Career development is the company's obligation to fulfill employee rights. So that employee commitment arises in the work process. Effective career development will result in job satisfaction and the form of reciprocity will make maximum efforts with all the abilities it has to complete its work tasks. Human Resources are important assets and act as the main driving factor in the implementation of all agency activities or activities, so they must be managed properly in terms of empowerment and capacity building. This research was conducted to collect readings and find out what are the effects of hard skills and soft skills on employee performance. This study uses the SLR (Systematic Literature Review) method. SLR is a research approach that involves the identification, evaluation, and interpretation of all relevant research results to answer a particular research question, theme, or phenomenon of relevance. Based on the results of 10 journals that researchers found, it is important for companies to increase empowerment, hard skills, and soft skills in an effort to improve employee performance. Employees must be more empowered in ways such as providing job delegation, talent coaching, education and development, so that each employee can be more empowered and develop.